Improved performance of electron cyclotron resonance heating by perpendicular injection in the Large Helical Device. (22nd December 2020) - Tsujimura, T.I.; Yanai, R.; Mizuno, Y.; Tanaka, K.; Yoshimura, Y.; Tokuzawa, T.; Nishiura, M.; Sakamoto, R.; Motojima, G.; Kubo, S.; Shimozuma, T.; Igami, H.; et al.
Abstract: A real-time interlock system for power injection in electron cyclotron resonance heating (ECRH) was developed to be applied to Large Helical Device (LHD) plasma. This system enabled perpendicular injection, thus improving the performance of ECRH more than has ever been achieved before in LHD. Perpendicular propagation of the electron cyclotron wave at 77 GHz became more insensitive to the effect of refraction in comparison to the conventional oblique propagation. The achieved central electron temperature in the case of perpendicular injection was approximately 2 keV higher than that in the case of standard oblique injection for a central electron density of 1 × 10 19  m −3 by 1 MW injection. With such improved performance of ECRH, high-density ECRH plasma of 8 × 10 19  m −3 was successfully sustained after the injection of multiple hydrogen ice pellets for the first time in LHD.